Nigeria Biannual Economic Update, April 2019 : Water Supply, Sanitation and Hygiene – A Wake-up Call - World Bank Group (World Bank, Washington, DC, 2019)
Nigeria's emergence from recession remains slow: real GDP grew by 1.9 percent in 2018. While this was above the 0.8 percent growth of 2017, it was below the population growth rate, government projections and pre-recession levels. The oil and gas sector reverted to contraction from the second quarter of the year and the non-oil economy was thus the main driver of growth in 2018. While agriculture slowed down significantly due to conflict and weather events, whose effects were not counteracted by direct interventions by the Central Bank of Nigeria (CBN), non-oil, non-agricultural growth, which remained negative up to the third quarter of 2017 strengthened through 2018 - but remained weak – with services (primarily ICT) resuming as the key driver. As the oil sector is not labor-intensive, and the non-oil economy was still relatively weak, nearly a quarter of the work force was unemployed in 2018; and another 20 percent under-employed. With 3.9 million net entrants into the labor force (now 90.5 million people) during 2018 (up to September) (4.5 percent growth), but virtually no growth in the stock of jobs, unemployment rose by 2.7 percentage points since end-2017, and more than doubled compared to the pre-recession levels (9.9 percent in Q3 of 2015).